The paradox of development initiatives and implementation issues in Zimbabwe - Muradya, T.; Modiba, F. S. (IPADA, 2019)
This paper explores issues surrounding development and sustainability of development projects in the African context. Africa is a young continent with regards to development. The continent continuously faces various challenges such as economic stagnation, high levels of poverty and unemployment, political instability as well as increasing inequality. Cognizant of these challenges, development aid and project implementation are thus seen as a panacea to poverty reduction and the gateway to development, as they have a potential to improve the livelihoods of African citizens. For instance, through the interaction and contribution of various actors within the development spectrum, development project implementation can improve conditions for these developing economies. This paper presents a case study of beneficiaries of the International Labour Organization's youth development programme in Zimbabwe where the programme's sustainability in reducing poverty and improving lives was assessed. A qualitative approach was utilized to attain in depth knowledge on the program, from the perspectives of beneficiaries. Data was analyzed using qualitative content analysis. Findings of the study portrayed various factors which hinder the success of development project implementation such as politicization of programmes, the unstable state of the economy, poor monitoring and evaluation systems and lack of financial support. The study recommended promoting formalisation of the informal sector, alleviating political interference in development programmes and community inclusion in all stages, supporting youth businesses and implementing strong monitoring and evaluation systems including measures that will address the widespread challenges impacting sustainable development in Africa. Keywords: Development, Evaluation, Informal economy, Monitoring, Poverty, Sustainable
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Development; Evaluation; Informal economy; Monitoring; Poverty; Sustainable; Sustainable development -- Zimbabwe; Developing countries; Economic development